Rancang Bangun Mesin Pengering Bibit Jahe Merah Menggunakan Sistem Blower di PT YRS - Yasmin Anisah; Fais Hamzah; Tri Tiyasmihadi (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
One of the problems of PT. YRS (Confident of Achieving Success) is the damage of red ginger seedlings due to a long period of time during the expedition so that the seeds of ginger decay. One of the decay factors is the high water content. To minimize damage to ginger seeds, red ginger seeds must be aerated (dried) for 1 week in 200 kg. The process is considered less efficient because it still uses manual methods. Therefore, an integrated machine is needed. This red ginger seed drying machine uses a fan blower system as an introduction to hot air with an air flow rate of 29 cfm and uses an automatic system as an electric controller. This ginger seed drying machine requires energy of 790 j / sec or 790 watts. The results in this study are that the red ginger seed drying machine can work well and can achieve drying of ginger seeds with an average moisture content of 83.17% where the moisture content is included in the specification requirements of PT. YRS within 45 minutes. This drying machine speeds up the drying process than before and cuts the operational costs of PT. YRS so that by using this tool PT. YRS can reduce expenses.